TINGKAT PENGETAHUAN PASIEN TB PARU BERHUBUNGAN DENGAN PELAKSANAAN STRATEGI DOTS - Tukatman, Tukatman; Yulianti, Sri; Baeda, Abd. Gani (Progres Ilmiah Kesehatan, 2021)
TB is an infectious disease which occurs in the respiratory system. Since the implementation of DOTS nationally in 2000 to 2014 has shown positive progress. However, there are still many challenges that must be faced by the government. One of them is the knowledge of TB sufferers themselves who still need to be improved regarding all matters relating to TB disease, especially regarding the DOTS strategy In 2015, the number of pulmonary TB patients treated at the Pipit Hospital in Anutapura General Hospital in Palu from January to May totaled 115 patients. Based on preliminary studies at Anutapura General Hospital, the majority of TB patients stated they did not know or had never heard of DOTS. They only know the common signs and symptoms of pulmonary TB, which are coughing for more than two weeks and know the combination of TB drugs that must be taken. This study aims to analyze the relationship between patient knowledge about pulmonary TB with the DOTS strategy. The design of this research is analytic with Cross Sectional approach. The population in this study was all patients in the Pipit treatment room at Anutapura General Hospital, Palu in January-March 2019, amounting to 114 people. The sample in this study was 24 people using simple random sampling technique. Data analysis use chi-square test. The results showed a relationship between the levels of knowledge regarding pulmonary tuberculosis with the DOTS strategy in Anutapura Regional Hospital in Palu (p-value = 0.011)